Cross-cultural adaptation and psychometric evaluation of the Chinese version of the sickness presenteeism scale- nurse (C-SPS-N): a cross-sectional study - Chuang Li; Zhi Xing Meng; You Bei Lin; Lan Zhang (BMC Nursing)
Abstract Background Currently, no standardized evaluation instrument exists to assess the impact of presenteeism on nurses’ productivity and the quality of care they provide. This study aimed to translate the Sickness Presenteeism Scale-Nurse (SPS-N) into Chinese and evaluate its reliability and validity among Chinese nurses. Methods This study first translated the 21-item English version of the SPS-N scale into Chinese using Brislin’s model. Then, six experts in the relevant field were invited to evaluate the item content validity index (I-CVI) of the translated scale. Using a convenience sampling method, 503 clinical nurses meeting the inclusion criteria were recruited from tertiary hospitals in Jinzhou, Liaoning Province, China. The reliability of the scale was assessed through internal consistency, split-half reliability, and test-retest reliability. To examine the structural validity of the Chinese version of the SPS-N (C-SPS-N), exploratory factor analysis (EFA) was conducted first, followed by confirmatory factor analysis (CFA) to further assess its construct validity. Results The C-SPS-N demonstrated strong psychometric properties, with a Cronbach’s α coefficient of 0.924. The item content validity index (I-CVI) for individual items ranged from 0.830 to 1.000. The split-half reliability was 0.750, and the test-retest reliability was 0.895. The four-factor exploratory factor model explained 78.354% of the total variance, indicating a robust factor structure. Confirmatory factor analysis (CFA) produced model fit indices of CMIN/DF = 2.527, RMSEA = 0.067, AGFI = 0.857, TLI = 0.941, IFI = 0.950, CFI = 0.949, GFI = 0.900, and PGFI = 0.692. All indices fell within acceptable ranges, confirming a satisfactory model fit. Both convergent validity and discriminant validity were adequately supported. Conclusion This study strictly adhered to the Brislin translation model and successfully introduced the SPS-N scale, which demonstrated strong reliability and validity in the Chinese cultural context. The Chinese version of the SPS-N (C-SPS-N) serves as an effective and reliable tool for assessing nurses’ presenteeism behaviors.